Evaluation of Silica-based Additives for Slagging Mitigation in Biomass Combustion: A Thermochemical Approach - Abdul Wahid Erlangga; Mochamad Zainudin Ade Arta; Muhammad Syarif Hidayatullah (Department of Mechanical and Industrial Engineering, 2026)
Slagging and fouling remain key barriers to reliable biomass cofiring in coal-fired boilers due to alkali-rich ashes that form low-melting deposits. This study evaluates a low-cost mitigation route using a 3 wt% natural soil additive (SiO₂–Al₂O₃ rich) and quantifies its impact on alkali release and slag formation for rice husk (RH), sawdust (SD), and empty fruit bunch (EFB). Thermodynamic-equilibrium calculations were performed in FactSage (FToxid + FactPS; Equilib module) over 500–1800 °C, using literature-based ultimate/oxide analyses normalized to 1,000 g fuel and combustion air with 15% excess. Volatile species (K, Na, KCl, NaCl, KOH, NaOH) and slag-phase oxides (K₂O, Na₂O) were tracked; ash-melting behavior was additionally probed under oxidizing and reducing atmospheres. The additive substantially suppressed alkali volatility for moderate-alkali biomasses. In RH, KCl(g) and KOH(g) declined by 40–45%, with 50% reduction in total gaseous alkalis. In SD, KOH(g) and K(g) fell by 52% and 46%, and slag-phase K₂O decreased by 51%, indicating stabilization via aluminosilicate formation. For EFB, the inherently high K limited mitigation: KOH(g) decreased 25%, while K₂O(s) increased 80%, evidencing partial capture but persistent high volatility. Overall, natural soil is a practical, locally available additive that can lower alkali volatilization by up to 50% for RH and SD, thereby reducing slagging/corrosion risk in cofiring. High-K EFB will likely require higher dosages, fuel blending, or pre-treatments. The results provide quantitative guidance for additive selection and dosing to enhance operational reliability in biomass cofiring.